Reading Guide and Students' Arabic Reading Ability - Desriliwa Ade Mela; Mamluatul Hasanah; Muhammad Fadli Ramadhan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Reading is one of the literacy skills set as Indonesia's national education goal and become a necessary skill in the 21st century. The reading skill of students of MTs Al-Hidayah Batu has not met the ideal standard. Achieving reading skills requires adequate vocabulary mastery and selecting appropriate methods. This study was designed to measure the influence of the reading guide method on students' knowledge of Arabic reading skills. The design of this study is quasi-experiments. There are 30 samples taken from a total population of 120 people using the purposive sampling technique. Data collected through tests, questionnaires, and interviews are analyzed using a t-test. The results show that the reading guide method can improve students' reading skills. Proven by the t-test result of the reading ability with a sig (2-tailed) value of 0.010 < 0.05. This statistical test implied that Ho was rejected. Ha is accepted, which means that there is a positive influence on the use of the reading guide method in improving students' reading skills, indicated by increasing the ability to read appropriately, mentioning the meaning of vocabulary in the text, answering questions based on the text, summarizing and retelling the content.